Jateng Explore (JX): Sustainable Tourism Digital Ecosystem Modelling based on Integrated Data and Payment Innovation - Pratama, Kristianus Jimy (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
Tourism plays a vital role in Central Java’s economy, yet its potential is constrained by fragmented data, uneven digital access, and limited MSME financial inclusion. This study introduces Jateng Explore (JX), a regional-scale digital public infrastructure model for sustainable tourism governance that integrates tourism services, MSMEs, and government coordination within a modular platform.. Developed through a design-based research approach, JX features smart modules including Destination Intelligence, Thematic Tourism Module, Halal & Inclusive Tourism Engine, Smart Booking, and a Digital MSME Marketplace. The platform incorporates AI-driven profiling, ESG gamification, and GIS-based analytics to enable personalized, equitable, and sustainable tourism experiences. The study’s originality lies in embedding data interoperability, sustainability-by-design, and financial inclusion within a public-sector-led smart tourism ecosystem, moving beyond fragmented or firm-centric platforms. It also aligns with national platforms like Satu Data Indonesia, positioning JX as a scalable model for smart tourism governance.